International Humanitarian Law Perspective on Un-Targeting Attack - Try Hardyanthi (Fakultas Hukum Universitas Muhammadiyah Magelang, 2021)
The Syrian conflict started on January 26th, 2011. At first, the conflict in Syria was an internal conflict between the government of Bashar Al Assad and the Rebel, the descent into war began with the violent and brutal repression of peaceful pro-reform protests, which later turned into an armed uprising against the regime of Bashar al-Assad, and has since become a regional conflict involving state and non-state actors. In the development of the conflict, some parties intervened to provide support for the Bashar al-Assad. One of the countries that intervene against Syria is Russia. In the armed conflict which happened in Syria on September 2015 and early October 2016, more than 9,000 people, including 4,000 Syrian civilians, were killed by the Russian airstrikes. The International Humanitarian Law hostilities regulate the protection of victims of conflict and restrictions on the means and methods of warfare. This study aims to identify the obstacles of legal enforcement of international humanitarian law toward un-targeting attack in Syria. In addition, this study tries to reveal the responsibility of these states, both Russia and Syria for the loss and injury caused by an un-targeting attack. The result shows that the obstacles of law enforcement in Syria case caused Syria is not a state party in several international conventions. Therefore, these conventions are not applicable formally in the armed conflict in Syria. Based on International Humanitarian Law, Syria Government is responsible for the un-targeting attack that occurred in Syria, and required to make full reparation for the loss or injury caused by such violations. They are required to make full reparation for the loss or injury caused by an un-targeting attack. Furthermore, Individuals belonging to an Organizations or State are held personally responsible before the law. Then, the United Nations Security Council (UNSC) must carry out UN Charter Articles 41 and 42 and UNSC as the main organ responsible for maintaining international peace and security.